(untitled) (Journal of the College of Basic Education, 2022)
The importance of the Egyptian University is highlighted by the great and essential role in spreading science and culture among the members of the Egyptian society, because of the capabilities, equipment and concerned professors it provided, and it achieved great success in this scientific field, and thanks to Prince Fouad the King later in building this great edifice and achieving overwhelming success.